Beginning Portable Shell Scripting - Seebach, Peter (Apress, 2012)
This book is about programming in the Bourne shell and its derivatives; the Korn shell, the Bourne- again shell, and the POSIX shell are among the most obvious relatives. This book does not cover the many other UNIX and UNIX- like shells, such as Plan 9’s rc, or the Berkeley csh. It does cover a number of common UNIX commands, as well as a few somewhat less common commands, and briefly looks into some common utilities, such as sed and awk, which have historically been used heavily in shell scripting. While even further divergent things, such as AppleScript, the Tcl shell, or even graphical shells like the Mac OS X Finder, are technically shells, this book ignores them entirely, and hereafter uses the term shell to refer to the UNIX Bourne shell family.